DAMPAK PERTUMBUHAN WAJIB PAJAK BADAN DALAM MENINGKATKAN PENERIMAAN PAJAK PENGHASILAN BADAN DI ERA COVID-19 PADA KANTOR PELAYANAN PAJAK PRATAMA SEKAYU KABUPATEN MUSI BANYUASIN - Farida Aryani (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2022)
This research is a descriptive research with analysis technique using calculation illustrated using charts to analyse the growth effects of corporate tax payer in increasing income tax receipt during Covid-19. The purpose of this research is to know the growth effects of corporate tax payer in increasing corporate income tax receipt during Covid-19 at KPP Pratama Sekayu Muba Regency. The data used is the corporate tax payer data registered and pay corporate income tax also the target and corporate income tax receipt realization from 2019-2021. The result of this research shows the growth of corporate tax payer increases significantly from 2019, that is in 2020 is 9.17% and in 2021 is 74.07%, thus during 2019-2021 the amount of corporate tax payer increases 83.24%. The increasing of corporate income tax receipt in 2020 gives negative effect to the corporate income tax receipt because the amount of income tax receipt realization during 2020 decreases 34.56%. This happens because the government sets the social distance policy to decrease Covid-19, thus some corporates stop their operation and cannot pay the tax. Meanwhile in 2021 the corporate income tax receipt realization is 95.49%. This shows that the increase of the tax payer amount gives positive effect to the increase of corporate income tax receipt 52.45%. This is caused by the tax amnesty policy and tax incentive as well as social distancing policy given, so that the economy of citizen is considered normal.